(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Custom-made orthotic insoles are routinely used in the treatment of the diabetic foot to reduce plantar pressure so as to minimise the risk of neuropathic ulceration. Due to the 3D geometry shape of the foot and insole, the measurement of the foot-orthosis interface pressure at different plantar regions in relation to insole material fabrication is vital for effective foot orthotic treatment. In the present study, a model of a custom-made three-layer contoured insole that simulates foot-insole interactions is developed by using finite element analysis. With the use of the insole material properties and plantar pressure distribution during balanced standing as the inputs, the magnitude of the deformity and the compressive stress distributed across the regions of the insole made of different combinations of materials are simulated. After validation, the simulated deformation shows good agreement with the result obtained by image processing technology. The simulation model not only provides a promising solution to the modification of materials for insoles by predicting and visualising insole deformation patterns, but also effectively optimises the design and development process of orthotic insoles without the need to fabricate and test the insoles in a series of wear trials.